Customer engagement in online service brand communities. Issue 2 (11th October 2021) - Chi, Ming; Harrigan, Paul; Xu, Yongshun
Abstract : Purpose: Online service brand communities (OBCs) are an essential services marketing channel and relationship marketing tool, in which social capital (SC) is a critical success factor. Underpinned in social identity and social exchange theories, this paper aims to explore the effects of SC on customer brand engagement (CBE), considering the roles of collective psychological ownership (CPO), customer citizenship behaviour (CCB) and perceived community support (PCS). Design/methodology/approach: The research model was tested using survey data from 256 participants; 137 from the Xiaomi Community and 119 from the Huawei Fan Club. Partial least squares-structural equation modelling analysis was used. Findings: SC drives CBE. CPO and CCB are important mediators, whilst PCS is an important moderator. Practical implications: Brand marketers need to foster SC in OBCs to achieve the maximum level of customer engagement. The authors provide recommendations as to how to build structural, relational and cognitive SC, as well as CPO, CCB and PCS. In short, brand marketers need to foster an interactive, empowering and supportive environment. Originality/value: The authors further service research around the humanisation of technology. Specifically, OBCs are social spaces for brands and customers, and a key enabler of relationship marketing principles, such as CBE. The authors test the roles of structural, cognitive and relational SC in engagement in OBCs, through CPO and CCB. This holistic picture of engagement in OBCs is an important foundation for future service research.